ECONOMIC AND ECOLOGICAL SUSTAINABILITY OF NON-TIMBER FOREST PRODUCTS (NTFPS) IN NIGERIA: A REVIEW - Adaaja, Blessing O.; Akemien, N. N.; Alawiye, M. A.; Zaman, E. Y.; Yahaya, U.; Khidir, H. Y. (FUDMA JOURNAL OF SCIENCES, 2024)
This study reviews the economic and ecological roles of Non-timber forest products (NTFPs) sustainability in Nigeria. Systematic review method was adopted for the study. The relationship between NTFPs trade, ecological conversation, socioeconomic benefits, poverty alleviation and sustainable forest management practice was carefully assessed. It was revealed that the NTFPs’ huge prospect and potential impact on the Nigeria economy largely depends on the ecological conditions, access to market, commercialization, value addition, its collection methods and utilization within and outside Nigeria. In addition, the review indicated that rural areas remain the hub for NTFPs trade and forest communities largely depend on it for their household income and livelihood. However, NTFPs could serve as a poverty trap for locals if the commercialization and value addition are not prioritized . In conclusion, this review underscores that the extent to which NTFPs can impact the economy cannot be fully studied unless those in the informal sector are well captured. In essence, NTFPs could serve as the key to unlock the economic growth of Nigeria through its huge revenue potential. Hence, the need for organizational, institutional and legal reforms that addresses the concerns of sustainable forest and NTFPs management within the ecosystem to achieve economic growth.
Keywords: NTFPs; Economic growth; Ecosystem; Sustainable Forest Management